CHEMICAL CHANGES AND SHELF LIFE FRUIT SALAK PONDOH (Salacca edulis REINW) DYNAMIC STORAGE IN THE AIR - CO2 - Kris Aji Adirahmanto; Rofandi Hartanto; Dwi Dian Novita (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2013)
Salak (Salacca edulis REINW) is an the original fruit from Indonesia. One of the most popular salak varieties is pondoh. The agribusiness opportunity of salak pondoh  is quite profitable, and therefore it is needed special handling to withstand and prolong shelf life. This study was conducted at the Laboratory of Bioprocess Engineering and Post Harvest Agricultural Engineering Department Agriculture Faculty, University of Lampung, October until December 2011. Treatment was carried out on 4 jars with CO2 gas discharge and air,and two temperature treatments, room temperature and cold temperature (10-12oC). The observed data rate of respiration, measurement of total dissolved solids and the calculation of the level of acidity. The results showed that (1) the measurement of respiration rates was fluctuate at the cooler temperatures storage than at room temperature, (2) The total dissolved solids of the two temperatures treatments were not  different, (3)  the level of acidity in the cold storage higher than at room temperature (4) storage temperature and composition was of the air - CO2 greatly influenced the shelf life and chemical changes. Keywords:Dynamic storage, Shelf life, Respiration,  Temperature, and Salak pondoh.